Age and sex related serum changes in nitric oxide and its correlation with plasma lipid profile and lipid peroxidation in healthy ageing individuals - Sheth, Rohit; Bhat, Tanmay; N., Suchetha Kumari; Ullal, Harshini Devi (International Journal of Advances in Medicine, 2017)
Background: The free radical theory of aging postulates that aging results from the accumulation of deleterious effects caused by free radicals, and the ability of an organism to cope with cellular damage induced by ROS plays an important role in determining organismal lifespan. GSH and SOD functions by donating the proton and in scavenging the superoxide radicals, thereby protecting the body against oxidative stress by scavenging the free radicals produced in the body. Glutathione peroxidase also have similar function, it reduce lipid hydroperoxides to their corresponding alcohols and free hydrogen peroxide to water. Methods: Hundred healthy adults from staff and student community under the age group of 20 to 60 years were recruited. Approximately 5ml blood sample was collected and used for the analysis of lipid profile, MDA and antioxidant status using standard protocol. Results: The lipid profile, MDA and antioxidant status were measured and compared with that of serum nitric oxide levels of 100 healthy individuals of the age 20-60 yrs. Men aged 20-29 years showed significantly higher NO levels compared to corresponding women. There is a significant reduction in total antioxidant capacity in elderly people. With the decrease in NO there is increase in MDA is observed. Conclusions: There is a significant reduction in total antioxidant capacity in elderly people. This reduction in antioxidant capacity implies a defect in antioxidant system, may be due to a reduction in individual antioxidant or may be caused by a non-equilibrium or poor cooperation between them.